BANGUN HUKUM AGRARIA NASIONAL BERBASIS NILAI-NILAI PANCASILA DI ERA GLOBALISASI - Sumarja, FX (Jurnal Media Hukum, 2012)
The study aims at knowing the implementation of Pancasila values in national agrarian law, national agrarian law from political perspective and the construction of national agrarian law in the globalization era. The result of study shows that Pancasila has rooted deeply in Agrarian Law Number 5 Year 1960. Accordingly it can be potential tools to explain, anticipate and provide solution for any legal problems in agrarian law issues in Indonesia. The Agrarian Law Number 5 Year 1960 as responsive political product of law is able to fulfill demand of justice of the society in Indonesia. Facing the globalization era, the agrarian law has to put Pancasila as the foundation which guides the law.Key words: Pancasila, Agraria Law, Building of Law